El portugués y la cultura lusófona: motivos para importarlos a Camerún - Onguédou Georges, Moukouti (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
The question one may ask himself, and which actually constitutes the backdrop of this paper is about the importance of teaching and learning a foreign language such as Portuguese in Cameroon, a country with more than two hundred and fifty local languages , alongside two foreign languages with official status: French and English. Importing Portuguese and Lusophone culture in Cameroon is timely, for many concrete and specific reasons. The first reason is the importance of Portuguese, moreover a language with an international status. Secondly, the weight of history, that of a country whose name we owe to the Portuguese explorers. In third place are the very important relationship between Cameroon and Brazil. Finally, what prevails is our educative policy consisting of rootedness in our own culture and openness to others and the world.
Keywords: Brazil; Cameroon; Lusophone culture; Portuguese; Import